2023
DOI: 10.1159/000528966
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Non-Gated Dynamic Fetal Cardiac MRI for Identification of Fetal Cardiovascular Anatomy

Abstract: Introduction: To evaluate the feasibility of identifying the fetal cardiac and thoracic vascular structures with non-gated dynamic balanced steady-state free precession (SSFP) MRI sequences. Methods: We retrospectively assessed the visibility of cardiovascular anatomy in 60 fetuses without suspicion of congenital heart defect. Non-gated dynamic balanced SSFP sequences were acquired in three anatomic planes of the fetal thorax. The images were analyzed following a segmental approach in consensus reading by an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…The weaker field strength reduces the likelihood of potential heating effects on the fetus and decreases the risks associated with strong magnetic field exposure [15]. Geiger et al [21] reported that fetuses examined at 1.5 T obtained a significantly higher imaging quality than at 3 T because of lower sensitivity to motion artifacts and fewer inhomogeneities of the radiofrequency field. In conclusion, 1.5 T CMR is usually sufficient to perform fetal CMR.…”
Section: Hardware Considerationmentioning
confidence: 99%
See 4 more Smart Citations
“…The weaker field strength reduces the likelihood of potential heating effects on the fetus and decreases the risks associated with strong magnetic field exposure [15]. Geiger et al [21] reported that fetuses examined at 1.5 T obtained a significantly higher imaging quality than at 3 T because of lower sensitivity to motion artifacts and fewer inhomogeneities of the radiofrequency field. In conclusion, 1.5 T CMR is usually sufficient to perform fetal CMR.…”
Section: Hardware Considerationmentioning
confidence: 99%
“…If the signal intensity is not adequate, the coil must be repositioned accordingly. Scout sequences are obtained in the three orthogonal planes of the mother's abdomen (axial, sagittal, and coronal) using 6-8 mm single-shot fast spin-echo (SSFSE) T2-weighted sections with a 1-2 mm gap and a large field of view (320-400 mm) [21].…”
Section: Hardware Considerationmentioning
confidence: 99%
See 3 more Smart Citations